2011
DOI: 10.1002/jclp.20800
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between the working alliance and social support on counseling outcome

Abstract: The purpose of this study was to test the impact of two predictor variables, one representing extratherapeutic factors and one representing relationship factors, on outcome at a university counseling training clinic. A naturalistic design was used to collect session-by-session outcomes on 135 clients seen by 88 counselors. Hierarchical linear modeling was used to test hypotheses about the effects of clients' pretreatment social support (extratherapeutic factor) and working alliance (relationship factor) at ses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 31 publications
0
19
0
1
Order By: Relevance
“…In recent years, a large number of studies have appeared in the literature that have used growth curve modeling to assess treatment outcome (e.g., Bornas, Gelabert, Llabrés, Balle, & Tortella‐Feliu, ; Elliott & Berry, ; Elliott, Berry, & Grant, ; Elliott, Brossard, Berry, & Fine, ; Johnson et al, ; Leibert, Smith, & Agaskar, ; Lutz et al, ; McClendon et al, ). For example, in Johnson et al's () aforementioned RCT of a treatment for PTSD symptoms among women in a battered women's shelter, the researchers assessed outcome variables at baseline and then again 1 week, 3 months, and 6 months after leaving the shelter.…”
Section: Overview Of Mlmmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, a large number of studies have appeared in the literature that have used growth curve modeling to assess treatment outcome (e.g., Bornas, Gelabert, Llabrés, Balle, & Tortella‐Feliu, ; Elliott & Berry, ; Elliott, Berry, & Grant, ; Elliott, Brossard, Berry, & Fine, ; Johnson et al, ; Leibert, Smith, & Agaskar, ; Lutz et al, ; McClendon et al, ). For example, in Johnson et al's () aforementioned RCT of a treatment for PTSD symptoms among women in a battered women's shelter, the researchers assessed outcome variables at baseline and then again 1 week, 3 months, and 6 months after leaving the shelter.…”
Section: Overview Of Mlmmentioning
confidence: 99%
“…Although our primary focus in this article is on RCTs, growth curve modeling may also be applied to data from naturalistic studies. Leibert et al () examined whether two common therapeutic factors–client social support and the therapeutic alliance–were associated with a change in OQ‐45 scores among 135 college students seen at a university counseling training center. OQ‐45 scores (the level‐1 dependent variable) were obtained before each session, and social support and the working alliance (the level‐2 independent variables) were assessed one time each.…”
Section: Overview Of Mlmmentioning
confidence: 99%
“…Measuring the effectiveness of counseling has progressed over the decades and is now a much more complex concept than simply comparing clients in treatment with those not receiving treatment. Beyond the aforementioned research on the therapeutic relationship and client outcomes, many factors were examined in searching for connections between extratherapeutic variables and counseling effectiveness, such as counselor attributes, anxiety levels of clients, social support, and the aforementioned therapeutic relationship (Ahn & Wampold, ; Barrett‐Lennard, ; Leibert, Smith, & Agaskar, ). In addition, given that counselors often overestimate client progress (Walfish, McAlister, O'Donnell, & Lambert, ), more formal feedback mechanisms are needed to accurately assess for therapeutic gains.…”
Section: Research On Client Outcomesmentioning
confidence: 99%
“…Common factors are the similarities between different theoretical models. They are the active elements or essential ingredients across all counseling and psychotherapy approaches (Frank and Frank, 1991;Leibert et al, 2011;Weinberger and Rasco, 2007). Strupp (2001) identified that the outcome of a counseling and/or therapeutic process was frequently affected by the personal characteristics of the counselor/therapist and the client's positive feelings-non-specific (common) factors-which can elicit the positive therapeutic emotional and interpersonal interactions.…”
Section: Common Factorsmentioning
confidence: 99%